2022
DOI: 10.3892/ol.2022.13530
|View full text |Cite
|
Sign up to set email alerts
|

The immune landscape of hepatocellular carcinoma‑where we are? (Review)

Abstract: Hepatocellular carcinoma (HCC) is one of the most common types of cancer diagnosed worldwide. After a decade of stagnation, several novel compounds have recently been shown to be effective in the treatment of HCC. Since immunotherapy is associated with important clinical benefits in some, but not all patients, it is essential to identify reliable predictive biomarkers. As the complex interplay between hepatocytes and immune cells is highly dependent on the tumor microenvironment, the tumor microenviroment has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…We also found evidence underlying the numerical correlation between immune cell infiltrates in HTS, such as CD4 T cells (memory and resting) and CD8 T cells, resting and activated NK cells, and monocytes and macrophages M0. Some of these have been previously reported and others remain to be confirmed [ [21] , [22] , [23] ]. We compared the differences in immune infiltrating cell composition between HTS and normal tissues.…”
Section: Discussionmentioning
confidence: 78%
“…We also found evidence underlying the numerical correlation between immune cell infiltrates in HTS, such as CD4 T cells (memory and resting) and CD8 T cells, resting and activated NK cells, and monocytes and macrophages M0. Some of these have been previously reported and others remain to be confirmed [ [21] , [22] , [23] ]. We compared the differences in immune infiltrating cell composition between HTS and normal tissues.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, immunotherapy has become a novel first-line treatment choice for advanced HCC ( Hilmi et al, 2019 ; Laface et al, 2022 ; Sangro et al, 2021 ). Studies have shown that infiltrating immunocytes in tumor tissue can interact with tumor cells and affect tumor progression, and can affect the prognosis of patients ( Dong et al, 2016 ; Gryziak et al, 2022 ; Pham et al, 2022 ; Sia et al, 2017 ). In particular, reports indicate that immunosuppressive tumor microenvironment due to tumor immunocyte infiltration can lead to poor prognosis ( Hoechst et al, 2008 ; Khanam & Kottilil, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of HCC, M1 polarized macrophages can impede tumor growth through various pathways, while their M2 counterparts are involved in promoting angiogenesis, which facilitates tumor development (Cheng et al, 2022). Neutrophils have a dualistic role in oncogenesis, as they can either stimulate or inhibit cancer progression, highlighting their complex relationship with tumor pathobiology (Gryziak et al, 2022). NK cells are known for their innate cytotoxic potential and play a crucial role in lymphocytemediated effector responses.…”
Section: Id Compound Structure 10 Deguelinmentioning
confidence: 99%